2020
DOI: 10.1101/2020.10.06.328112
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Proteoforms of the SARS-CoV-2 nucleocapsid protein are primed to proliferate the virus and attenuate the antibody response

Abstract: The SARS-CoV-2 nucleocapsid (N) protein is the most immunogenic of the structural proteins and plays essential roles in several stages of the virus lifecycle. It is comprised of two major structural domains: the RNA binding domain, which interacts with viral and host RNA, and the oligomerization domain which assembles to form the viral core. Here, we investigate the assembly state and RNA binding properties of the full-length nucleocapsid protein using native mass spectrometry. We find that dimers, and not mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 51 publications
(48 reference statements)
0
14
0
Order By: Relevance
“…17/19, 69/71), consistent with a degree of further exoproteolytic processing. Some of these cleavage sites have subsequently been identified as autolysis products following extended incubations with N in vitro (26).…”
Section: Resultsmentioning
confidence: 99%
“…17/19, 69/71), consistent with a degree of further exoproteolytic processing. Some of these cleavage sites have subsequently been identified as autolysis products following extended incubations with N in vitro (26).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the few biophysical studies that incorporate RNA binding, either on individual domains or FL-N, have been limited to short segments of RNA or to synthesized polynucleotide RNA models rather than the viral RNA (11,12,14,43). These limited and conflicting reports are not surprising considering that the FL-N is a large multidomain protein with three long disordered segments and is prone to autoproteolysis (46) and aggregation as well as nonspecific binding to bacterial proteins and RNA during recombinant expression and purification, as we find in our studies. Our work here, to our knowledge, offers the first thorough characterization of FL-N and its binding to a 1000-nt segment of the viral RNA and presents a model that explains the importance of FL-N bivalent structure to enhancing its binding affinity on multivalent sites of a long segment of the viral RNA.…”
Section: Discussionmentioning
confidence: 99%
“…N2 has been described using both X-ray crystallography (Kang et al 2020;Peng et al 2020) and NMR spectroscopy (Dinesh et al 2020). The dimerization domain N4 has been described using X-ray crystallography (Ye et al 2020;Peng et al 2020) and N has been shown to form higher order oligomers via N4 (Ye et al 2020;Zeng et al 2020;Lutomski et al 2020). The remaining 164 amino acids comprising N1, N3 and N5 are predicted to be intrinsically disordered, but despite evidence that these domains are essential for function in the related Mouse Hepatitis virus (Keane and Giedroc 2013), there is currently no atomic resolution information describing their behaviour in solution.…”
Section: Biological Contextmentioning
confidence: 99%
“…Peptides representing the SR region of N3 in its phosphorylated and non-phosphorylated forms were also described using NMR spectroscopy (Savastano et al 2020 ). Mass spectrometry has also revealed a number of auto-catalytic sites in N, two of which are present in N3 (Lu et al 2020 ; Lutomski et al 2020 ).…”
Section: Biological Contextmentioning
confidence: 99%